PROBLEMS AND PROSPECTS OF SMALL AND MEDIUM BUSINESSES IN RUSSIA - I. N. Ivanov; T. V. Lukyanova; L. V. Orlova (Вестник университета)
The main features of small and medium-sized businesses and the conditions for their functioning in Russia have been considered. A significant lag of the Russian Federation in terms of the development of small and medium-sized businesses from economically advanced countries has been noted. The sectoral structure of domestic small and medium-sized businesses, its contribution to the country’s economy have been highlighted. The main problems hindering the development of small and medium-sized businesses in Russia have been analysed. In particular, a shortage of credit and financial resources, an imperfection of the taxation system, excessive business administration, overpriced compulsory insurance payments, a lack of readiness of a significant part of small and medium-sized businesses management to conduct business, have been revealed. The main activities carried out by the state to support small and medium-sized businesses have been enumerated, inconsistency and insufficiency of these activities have been enumerated. As the main way of state support for small and medium-sized businesses, it has been proposed to create favorable conditions for conducting its activity, including further improvement of tax legislation in this field, facilitating their access to loans, eliminating unnecessary regulatory, administrative and organizational barriers, training and advanced training for management.